PERBANDINGAN PENGGUNAAN KALSIUM KARBONAT DAN NATRIUM KARBONAT DALAM PEMISAHAN CANGKANG DAN KERNEL - Sari, Vonny Indah (Jurnal Teknologi Pertanian, 2013)
Clay bath is where the separation of the shell, core nucleus intact and broken. The process of separation occurs because of differences in density between the core with the shell with the help of a solution of CaCO3. Core with a lighter density in the solution of CaCO3 floats and shells with a greater specific gravity settle to the bottom. This process is carried out in a cone-shaped vessel is equipped with a pump to circulate CaCO3. The existence of the circulation of fluid motion will bring the kernel into the sieve vibration to be cleaned and then sent to the kernel in the Kernel Wet Fan heading to Kernel Shiloh to the heat. This reseach compared the performance of the solution with a solution of Na2CO3 and CaCO3 in their shells and kernels, seen from the solubility rate between kalsim carbonate and sodium carbonate in water